THE RELATIONSHIP OF FAMILY ROLES WITH EVENTS STUNTING IN TODDLER AGES 0-5 YEARS IN LIMBUNG VILLAGE, SUNGAI RAYA DISTRICT, KUBU RAYA DISTRICT, WEST KALIMANTAN - Rosfiana, Sebti; Amelia, Lince; Hidayah, Hidayah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The Ministry of Health announced the SSGI which shows the prevalence stunting West Kalimantan in 2022 will be 27.8% and is among the 10 provinces with prevalence stunting tall. Kubu Raya District Health Service prevalence of toddlers stunting Based on the SSGI in 2023, the highest village or subdistrict is in Limbung Village at 29.4%. This study aims to determine the relationship between the role of the family and the incidence of stunting in toddlers aged 0-5 years in Limbung Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan. This research uses observational analytics with a design approach case control restrospektif. The sampling technique is accidental sampling The sample consisted of 41 controls and 41 cases. Univariate analysis in this study used descriptive statistical tests and bivariate analysis in this study used tests rank Spearman. The results of the research obtained the role of families in Limbung Village in the child case group stunting more of them played a bad role with 24 respondents (48.6%) and in the control group children who did not experience stunting played more of a good role with 41 respondents (100%). The Spearman test results have a value of 0.000 <0.05, there is a relationship between the role of the family and the incident stunting. Mark Sig.(2-tailed) of 0.000, because of the value of the value Sig.(2-tailed) < 0.05 means there is a significant relationship between variables X and Y and the correlation coefficient is -643**. There is a relationship between the role of the family and the incident stunting in toddlers aged 0-5 years in Limbung Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan.